Mating activates the heme peroxidase HPX15 in the sperm storage organ to ensure fertility in Anopheles gambiae - Shaw, W Robert; Teodori, Eleonora; Mitchell, Sara N; Baldini, Francesco; Gabrieli, Paolo; Rogers, David W; Catteruccia, Flaminia (Proceedings of the National Academy of Sciences - PNAS, 2014)
Anopheles gambiae mosquitoes are major African vectors of malaria, a disease that kills more than 600,000 people every year. Given the spread of insecticide resistance in natural mosquito populations, alternative vector control strategies aimed at reducing the reproductive success of mosquitoes are being promoted. Unlike many other insects, An. gambiae females mate a single time in their lives and must use sperm stored in the sperm storage organ, the spermatheca, to fertilize a lifetime's supply of eggs. Maintenance of sperm viability during storage is therefore crucial to the reproductive capacity of these mosquitoes. However, to date, no information is available on the factors and mechanisms ensuring sperm functionality in the spermatheca. Here we identify cellular components and molecular mechanisms used by An. gambiae females to maximize their fertility. Pathways of energy metabolism, cellular transport, and oxidative stress are strongly regulated by mating in the spermatheca. We identify the mating-induced heme peroxidase (HPX) 15 as an important factor in long-term fertility, and demonstrate that its function is required during multiple gonotrophic cycles. We find that HPX15 induction is regulated by sexually transferred 20-hydroxy-ecdysone (20E), a steroid hormone that is produced by the male accessory glands and transferred during copulation, and that expression of this peroxidase is mediated via the 20E nuclear receptor. To our knowledge, our findings provide the first evidence of the mechanisms regulating fertility in Anopheles, and identify HPX15 as a target for vector control.